Assertiveness in the patients with thalassaemia major: A qualitative study - Leila Valizadeh; Vahid Zamanzadeh; Akram Ghahramanian; Soghra Hasani Narenjbaghi (Wiley, 2021)
Abstract Aim To explore the concept of assertiveness in the patients with thalassaemia major. Design It was a qualitative study with a conventional content analysis design. Method Data were collected using a semi‐structured interview. The research sample included 16 patients with thalassaemia major who were selected using purposeful sampling method from among such patients at educational and therapeutic centres. Then, they were analysed using MAXQDA10 software. Results During the analysis of data for the concept of assertiveness, three sub‐concepts of "courage to self‐presentation," "demonstrating the abilities" and "attendance in groups" were developed.